Altered skeletal muscle glucose–fatty acid flux in amyotrophic lateral sclerosis. Issue 2 (24th September 2020) - Steyn, Frederik J; Li, Rui; Kirk, Siobhan E; Tefera, Tesfaye W; Xie, Teresa Y; Tracey, Timothy J; Kelk, Dean; Wimberger, Elyse; Garton, Fleur C; Roberts, Llion; Chapman, Sarah E; Coombes, Jeff S; et al.
Abstract: Amyotrophic lateral sclerosis is characterized by the degeneration of upper and lower motor neurons, yet an increasing number of studies in both mouse models and patients with amyotrophic lateral sclerosis suggest that altered metabolic homeostasis is also a feature of disease. Pre-clinical and clinical studies have shown that modulation of energy balance can be beneficial in amyotrophic lateral sclerosis. However, the capacity to target specific metabolic pathways or mechanisms requires detailed understanding of metabolic dysregulation in amyotrophic lateral sclerosis. Here, using the superoxide dismutase 1, glycine to alanine substitution at amino acid 93 (SOD1 G93A ) mouse model of amyotrophic lateral sclerosis, we demonstrate that an increase in whole-body metabolism occurs at a time when glycolytic muscle exhibits an increased dependence on fatty acid oxidation. Using myotubes derived from muscle of amyotrophic lateral sclerosis patients, we also show that increased dependence on fatty acid oxidation is associated with increased whole-body energy expenditure. In the present study, increased fatty acid oxidation was associated with slower disease progression. However, within the patient cohort, there was considerable heterogeneity in whole-body metabolism and fuel oxidation profiles. Thus, future studies that decipher specific metabolic changes at an individual patient level are essential for the development of treatments that aim to target metabolic pathways in amyotrophic lateral sclerosis. Abstract : In superoxide dismutase 1, glycine to alanine substitution at amino acid 93 (SOD1 G93A ) mice, increased whole-body metabolism occurs alongside fat depletion and increased fatty acid oxidation in glycolytic muscle. Myotubes from patients with amyotrophic lateral sclerosis have increased fatty acid oxidation, and this is associated with increased whole-body energy expenditure. Increased fatty acid oxidation may sustain energy supply to slow disease. Graphical Abstract: